A molecular phylogeny of the Grunts (Perciformes: Haemulidae) inferred using mitochondrial and nuclear genes - Sanciangco, Millicent D.; Rocha, Luiz A.; Carpenter, Kent E. (Zootaxa, 2011)
We infer a phylogeny of haemulid genera using mitochondrial COI and Cyt b genes and nuclear RAG1, SH3PX3, and Plagl2 genes from 56 haemulid species representing 18 genera of the expanded haemulids (including the former inermiids) and ten outgroup species. Results from maximum parsimony, maximum likelihood, and Bayesian analyses show strong support for a monophyletic Haemulidae with the inclusion of Emmelichthyops atlanticus. The former inermiids did not form a clade indicating that the highly protrusible upper jaw specialization to planktivory evolved more than once within Haemulidae. The subfamilies Haemulinae and Plectorhinchinae, currently diagnosed by eight morphological characters, most notably the number of chin pores and the origin of the retractor dorsalis, are also recovered from these analyses with the Haemulinae sister to the Plectorhinchinae. Plectorhinchus is monophyletic only with the inclusion of Diagramma. Within the Haemulinae, Pomadasys and Conodon are polyphyletic. In addition, Anisotremus is monophyletic only with the inclusion of Genyatremus and Conodon nobilis, and Haemulon is monophyletic only with the inclusion of Xenistius. These results suggest that further morphological and molecular studies are needed to revise the limits of several haemulid genera.